Implementasi Kurikulum Merdeka Belajar Berwawasan Moderasi Beragama di Sumenep - Abd Warits; Moh Asy'ari Muthhar (GUYUB: Journal of Community Engagement, 2024)
The emergence of intolerant understanding is due to the belief that only one's religious understanding is the most correct, while other beliefs are wrong. This phenomenon causes some people to feel "deserved" to give strict warnings, and not a few feel entitled to punish others who disagree. Therefore, intolerant understanding cannot only be resolved through seminars or workshops, but needs to be carried out massively in learning activities. The content of learning materials that have nuances of violence in religion must be balanced with an understanding to respect and care for each other. This community service activity seeks to instill the spirit of religious moderation in the learning process in the classroom which begins with compiling learning modules with nuances of moderation. Religious teachers who have been familiar with religious studies are trained and equipped with the values and character of moderation in order that they can implement independent curriculum learning based on moderation. The impacts of this community service include the preparation of Document 1 of the Independent Curriculum, the Draft Module for Religious Learning for Independent Curriculum based on Religious Moderation, and mapping of several discussions in religious materials that have the potential to give rise to extreme thoughts, including jihad, stories of war, prohibition of befriending non-Muslims, and leadership selection in Islam.